2023
DOI: 10.1002/smll.202300347
|View full text |Cite
|
Sign up to set email alerts
|

Thin Zinc Oxide Layer Passivating Bismuth Vanadate for Selective Photoelectrochemical Water Oxidation to Hydrogen Peroxide

Abstract: Selective photoelectrochemical (PEC) water oxidation to hydrogen peroxide is an underexplored option as opposed to the mainstream oxygen reduction reaction. Albeit interesting, selective H2O2 production via oxidative pathway is plagued by the noncontrollable two‐electron transfer reaction and the overoxidation of the thus‐formed H2O2 to O2. Here, ZnO passivator‐coated BiVO4 photoanode is reported for selective PEC H2O2 production. Both the H2O2 selectivity and production rate increase in the range of 1.0–2.0 V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 54 publications
(57 reference statements)
0
12
0
Order By: Relevance
“…Copyright 2022 Nature Publishing Group. (j) Reprinted with permission from ref . Copyright 2023 Wiley-VCH.…”
Section: Development Of Anodic H2o2 Generation Via Ec/pecmentioning
confidence: 99%
See 2 more Smart Citations
“…Copyright 2022 Nature Publishing Group. (j) Reprinted with permission from ref . Copyright 2023 Wiley-VCH.…”
Section: Development Of Anodic H2o2 Generation Via Ec/pecmentioning
confidence: 99%
“…Qu et al. designed a feasible photocatalyst with satisfied selectivity of H 2 O 2 production . They fabricated BiVO 4 upon ZnO overlayer coating of the photoanode, facilitating H 2 O 2 generation and suppressing the competitive reaction of O 2 evolution.…”
Section: Strategies To Enhance H2o2 Production Efficiency Through Pecmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Sayama et al found that the HCO 3 – electrolyte could promote the water oxidative H 2 O 2 formation in the photoelectrochemical (PEC) cell in 2016, PEC water oxidative H 2 O 2 production has been attracting great attention to pair with H 2 evolution and other interest reduction reactions due to the outstanding features of faster reaction kinetics, higher value-added, and easier separation of gas/liquid products compared to conventional oxygen evolution reaction (OER). The role of HCO 3 – was determined as an “Electron Donor”, which is first oxidized to HCO 4 – and then hydrolyzes H 2 O to return the HCO 3 – and produce H 2 O 2 . , Although some strategies, such as heterojunction construction, , surface passivation, , wettability regulation, , etc., have been developed to enhance the performance of H 2 O 2 production in the HCO 3 – -containing electrolyte, the selectivity of H 2 O 2 product leaves room to be improved due to the higher redox potential of HCO 3 – /HCO 4 – (1.8 ± 0.1 V vs normal hydrogen electrode (NHE)) than that of OER. , An understandable strategy for enhancing the HCO 3 – oxidation kinetics is to increase the HCO 3 – concentration in the electrolyte . However, for most bicarbonates, the solubility is limited to about 1.0 M.…”
Section: Introductionmentioning
confidence: 99%
“…2−5 The role of HCO 3 − was determined as an "Electron Donor", which is first oxidized to HCO 4 − and then hydrolyzes H 2 O to return the HCO 3 − and produce H 2 O 2 . 6,7 Although some strategies, such as heterojunction construction, 8,9 surface passivation, 10,11 wettability regulation, 12,13 etc., have been developed to enhance the performance of H 2 O 2 production in the HCO 3 − -containing electrolyte, the selectivity of H 2 O 2 product leaves room to be improved due to the higher redox potential of HCO 3 − /HCO 4 − (1.8 ± 0.1 V vs normal hydrogen electrode (NHE)) than that of OER. 14,15 An understandable strategy for enhancing the HCO 3 − oxidation kinetics is to increase the HCO 3 − concentration in the electrolyte.…”
Section: Introductionmentioning
confidence: 99%